Increased expression of dendrin in the dorsal horn of the spinal cord during stress is regulated by sex hormones. (April 2021) - Jurić, Marija; Balog, Marta; Ivić, Vedrana; Bošković, Maria; Benzon, Benjamin; Racetin, Anita; Vukojević, Katarina; Bočina, Ivana; Kević, Nives; Restović, Ivana; Szűcs, Kálmán F.; Gáspár, Róbert; et al.
Abstract: Chronic stress has various effects on organisms and is sex-specific. The aim of the study was to describe the expression of synapse strengthening protein, dendrin, in the spinal cord (SC) and the dependence of its expression on chronic stress and sex hormones. Thirteen-month-old female and male rats were castrated (ovariectomy [F-OVX] or orchidectomy [M-ORX]) or sham-operated (F-SH or M-SH), respectively. At age 15 months, three 10-day-sessions of sham stress (control, C) or chronic stress (S) were conducted. Dendrin expression was present in the thoracic SC segments and the dorsal root ganglia (DRG). In the SC, dendrin expression was prominent in superficial laminae of the dorsal horn and lamina X (central canal). The M-ORX-S group had the highest dendrin expression in the dorsal horn, being significantly higher than the M-ORX-C or M-SH-S groups ( P < 0.05). Dendrin expression was significantly higher in the F-SH-S group than the F-SH-C group ( P < 0.05), as well as in the F-SH-S than the M-SH-S ( P < 0.05). Co-localization with the α-d-galactosyl-specific isolectin B4 (IB4) in central projections of the DRG neurons in the dorsal horn of the SC was 7.43 ± 3.36%, while with the calcitonin gene-related peptide (CGRP) was 8.47 ± 4.45%. Localization of dendrin was observed in soma and nuclei of neurons in the dorsal horn. Dendrin expression in pain-processing areas of the SC, the DRG neurons and their peripheral projections suggest possible roles in pain perception and modulation. Stress-induced increase in dendrin expression and its dependence on sex hormones may partially explain sex-specific pain hypersensitivity induced by stress.